THE REAL-TIME WATER DISCHARGE COMPUTATION IN THE CONDITIONS OF UNSTEADY FLOW (THE YANA RIVER IN THE VERKHOYANSK GAGING SECTION AS A STUDY CASE) - Yulia V. Izyurova (Водное хозяйство России: проблемы, технологии, управление)
The real-time water discharge computation involves practical real-time computation of water discharge values to ensure forecasting and preventing dangerous hydrological phenomena, as well as daily monitoring of river water content and information support for the functioning of water management facilities in river basins. Nowadays the task of the real-time discharge accounting is very relevant. The article presents the outcomes of the study of two methods of computation of the real-time water discharges in the conditions of the unsteady flow that enable to pass to automatic operative accounting of the river flow. The first method is based on using of optimal extrapolation of the relative deviations of the measured water discharges from the reference rating curve obtained from the data of water discharge measurements for previous years. The second method is a new approach based on the Jones formula. The parameters of the Jones formula were obtained from measurements of water discharge over the past years using an optimization tool based on the generalized reduced gradient method. The daily real-time water discharges calculated in two ways were compared with the daily water discharges published in the reference books of the water cadaster «Daily data on the regime and resources of land surface waters». As a result, it was found that both methods can be used for automated real-time water discharge computation in conditions of unsteady flow.